Drivers of organizational commitment and job satisfaction among lodging industry employees / Aladin M. Ibrahim - M. Ibrahim, Aladin (UiTM Press, 2019)
This study focused primarily on determining the relationship and influence of job satisfaction dimensions on organisational commitment among lodging employees. This study employed a quantitative research design and data were collected from 290 front-line employees of the Department of Tourism’s accredited lodging facilities in South Cotabato Province, Sarangani Province, and General Santos City (SOCSARGEN), Philippines area using the convenience sampling. Data analysis showed that employee pay, promotion opportunities, supervision, fringe benefits, contingent rewards, relationship with co-workers, nature of work, and communication were among the dimensions of employee job satisfaction that were positively related with organisational commitment. Operating procedures showed a negative relationship with organisational commitment. Only the nature of work, promotion opportunities, and relationships with co-workers, operating procedures, and supervision from the facets of employee job satisfaction posted as significant predictors of organisational commitment.